Pengaruh Penggunaan Media Berbasis Information And Communications Technology (ICT) Terhadap Hasil Belajar Peserta Didik - Putri Rosary; Ivan Stevanus (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2023)
The use of the ICT-based learning media has been an integrated element in the learning design to help students achieve the learning objectives. The purpose of the study was to describe the effect of using the ICT-based learning media towards the learning outcomes of students in the social studies subjects for grade 5 in Duri Kosambi 10 Pagi Elementary School. This research is an experiment with a nonequivalent control group design. The data collection techniques were tests, interviews, and observations. The pretest score from the experimental class was 30.89 and 27.67 from the control class. The post-test scores from the experimental class was 83.39 and the control class obtained 73.33. Then the t-test using IBM SPSS Statistic 24, showed a significance value of 0.01 < 0.05. The results of interviews and observations showed a positive influence on learning interest and interaction of the students in the classroom, as evidenced by increased learning outcomes in the experimental class.